Evaluation of Marginal Adaptation of Root-End Filling Materials Using Scanning Electron Microscopy - Oliveira, Helder Fernandes; Alencar, Ana Helena Gonçalves; Figueiredo, José Antônio Poli; Guedes, Orlando Aguirre; Decurcio, Daniel de Almeida; Estrela, Carlos (Iranian Endodontic Journal, 2013)
Introduction: The importance of perfect apical seal in endodontics, more specifically in periradicular surgery, is the motivation/reason for development of root-end filling materials with favorable physical, chemical and biological characteristics. The aim of this in vitro study was to evaluate the marginal adaptation of root-end filling materials using scanning electron microscopy. Materials and Methods: Twenty five human maxillary anterior teeth were prepared using a K-File #50 to 1 mm short of the apical foramen and filled with gutta-percha and Sealapex using the lateral compaction technique. The apical 3 mm of the roots were sectioned perpendicularly to the long axis of the teeth. A 3-mm-deep root-end cavity was prepared using ultrasonic tips powered by an Enac ultrasonic unit. The teeth were randomly assigned to five groups according to the materials tested including IRM, amalgam, ProRoot MTA, Super-EBA and Epiphany/Resilon. Root-end cavities were filled with the materials prepared according to the manufacturers’ instructions. The root apices were carefully prepared for sputter coating and later evaluation using Scanning Electron Microscope (SEM). The images of root-end fillings were divided into four quadrants and distributed into five categories according to the level of marginal adaptation between the root-end material and the root canal walls. The Fisher exact test with Bonferroni correction was used for statistical analysis. The level of significance was set at P=0.005. Results: SEM images showed the presence of gaps in the root-end filling materials. No significant difference was observed between the tested materials (P>0.005). Conclusion: ProRoot MTA, IRM, amalgam, Super-EBA and Epiphany/Resilon showed similar marginal adaptation as root-end filling materials.